Reliving the Trenches : Memory Plays by Veterans of the Great War - Jauvoish, Simon; Atkinson, William Stabler, 1891-1963; Scudamore, H. B.; Filewod, Alan, 1952- (Book collections on Project MUSE., 2021)
"In Reliving the Trenches, three plays written by returned soldiers who served in the Great War with the Canadian Expeditionary Force in France and Belgium appear in print for the first time. With a critical introduction that references the authors' service files to establish the plays as memoirs, these plays are an important addition to Canadian literature of the Great War. Important but overlooked war memoirs that relive trench life and warfare as experienced by combat veterans, the three plays include The P.B.I., written and staged in 1920 by recently returned veterans at the University of Toronto. Parts of this play appeared in print in serial form in 1922. Glory Hole, written in 1929 by William Stabler Atkinson, and Dawn in Heaven, written and staged in Winnipeg in 1934 by Simon Jauvoish, have never been published. These plays impact Canadian literature and theatre history by revealing a body of previously unknown modernist writing, and they impact life writing studies by showing how memoirs can be concealed behind genre conventions. They offer fascinating details of the daily routines of the soldiers in the trenches by bringing them back to life in theatrical re-enactment."--